2016
DOI: 10.1016/j.pmrj.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Visualization of Thenar Motor Branch of the Median Nerve: A Cadaveric Validation Study

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
(135 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, a recently published level 1 prospective randomized controlled trial comparing mini‐open CTR (n = 41) with USCTR (n = 41) using a hook knife reported a 5‐time faster functional recovery and pain medication discontinuation with USCTR [4]. In addition to faster recovery, US provides an additional safety factor by visualizing of space‐occupying lesions and at‐risk structures, such as gouty tophi, ganglia, lipomas, fibromas, persistent median arteries, accessory muscles, and the palmar cutaneous and thenar motor branches of the median nerve [16,22,23]. Because of the ability to identify these at risk or aberrant structures before any procedures, USGCTR is potentially safer than traditional releases [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recently published level 1 prospective randomized controlled trial comparing mini‐open CTR (n = 41) with USCTR (n = 41) using a hook knife reported a 5‐time faster functional recovery and pain medication discontinuation with USCTR [4]. In addition to faster recovery, US provides an additional safety factor by visualizing of space‐occupying lesions and at‐risk structures, such as gouty tophi, ganglia, lipomas, fibromas, persistent median arteries, accessory muscles, and the palmar cutaneous and thenar motor branches of the median nerve [16,22,23]. Because of the ability to identify these at risk or aberrant structures before any procedures, USGCTR is potentially safer than traditional releases [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has resulted in a reduction in morbidity and an acceleration in recovery time due to the smaller incision size. 8 Transection of the retinaculum takes place after introduction of an endoscope with a retractable blade through a 1.5-to 2-cm incision in the wrist flexion crease. A break from work and daily activities of around 2 to 3 weeks is then recommended.…”
Section: Endoscopic Proceduresmentioning
confidence: 99%
“…Several studies have recently demonstrated the interest of ultrasound-guided transection of the retinaculum. [2][3][4][5][6][7] This technique has the advantages of (1) great safety, due to continuous ultrasound monitoring and visualization of variants of the median nerve, [8][9][10] and (2) a decrease in size of the incision, enabling a more rapid return to work and a more aesthetic scar. 6,11 Percutaneous access by ultrasound-guided surgery (UCTR) is, at least, 10 times smaller than with classical surgical techniques.…”
Section: Ultrasound-guided Surgerymentioning
confidence: 99%
“…The small motor branch of the median nerve arises at the level of the carpal tunnel and provides innervation to the muscles of the thenar eminence. Its US appearance has been recently described . Due to its variable origin, the nerve can be injured during a carpal tunnel release.…”
Section: Pathologic Us Findingsmentioning
confidence: 99%
“…Its US appearance has been recently described. [37][38][39] Due to its variable origin, the nerve can be injured during a carpal tunnel Figure 19. Complete section of the radial collateral nerve of the thumb after surgical treatment of trigger thumb syndrome.…”
Section: After Surgerymentioning
confidence: 99%